The Relationship between Hydro-Agricultural Drought in the Corong River Basin: A Causal Time Series Regression Model - Nur Azizah Affandy; Data Iranata; Nadjadji Anwar; Mahendra Andiek Maulana; Wasis Wardoyo; Dedy Dwi Prastyo; Bangun Muljo Sukojo (Civil Engineering Dimension, 2024)
This research explores the relationship between hydrological drought and agricultural drought in the Corong River Basin, focusing on the Gondang Reservoir Irrigation Area, Indonesia. By employing a Causal Time Series Regression Model, the study uncovers that agricultural drought twelve months prior has a significant impact on current agricultural drought and is influenced by current hydrological drought. Time series regression analysis reveals that 45.86% of agricultural drought is influenced by hydrological drought, with 54.14% influenced by other factors besides rainfall. Further research is needed to investigate these additional factors. These findings have practical implications, serving as a valuable index for assessing drought severity and planning mitigation actions, especially in the irrigation areas of interest. They emphasize the importance of effective irrigation management, appropriate cropping patterns, and a comprehensive understanding of the complex characteristics of drought in agricultural regions through comprehensive monitoring efforts in agricultural drought mitigation.